Drought coping strategies followed by dairy farmers in Bundelkhand region of Uttar Pradesh - SANKHALA, GOPAL; SINGH, MANESH; KANT, KAMALA; PRASAD, KAMTA (The Indian Journal of Animal Sciences, 2016)
Rainfed agriculture is highly risky, however, the livelihood of millions of resource poor farmers and agricultural labourers depends on it. The risks associated to agriculture in rainfed areas is increasing due to the adversities induced by climate variability indicated by increased frequency of droughts and floods. This paper analyzes the drought coping strategies followed by dairy farmers in Bundelkhand region of Uttar Pradesh utilizing a descriptive research design. Data were collected through personal interview and focus group discussion using both qualitative and quantitative techniques. The data were analyzed using frequency and percentage. The findings of present investigation show that majority of the farmers could not grow fodder crops during drought. However, they try to cope with drought by adopting strategies such as storing wheat straw and other crop residues (gram/lentil/mustard/linseed, etc.) in advance for meeting their feed shortage; providing feed and water twice a day and using crop residues (wheat straw/bhusa, paddy straw, jowar stover).